Phosphorescent platinum(ii) complexes bearing pentafluorosulfanyl substituted cyclometalating ligands12. Issue 41 (12th May 2017) - Henwood, Adam F.; Webster, James; Cordes, David; Slawin, Alexandra M. Z.; Jacquemin, Denis; Zysman-Colman, Eli
Abstract : The first examples of phosphorescent platinum(ii ) complexes bearing pentafluorosulfanyl (–SF5 ) substituted cyclometalating ligands (C^N) are reported. Abstract : The first examples of phosphorescent platinum(ii ) complexes bearing pentafluorosulfanyl (–SF5 ) substituted cyclometalating ligands (C^N) are reported. These complexes are of the form [Pt(C^N)(pivacac)], where pivacac is 2, 2′, 6, 6′-tetramethylheptane-3, 5-dionate. Modifying the phenyl ring of the C^N ligand to incorporate one strongly electron-withdrawing –SF5 group has important effects on the photophysical and electrochemical properties of the complex that are dependent on the regiochemistry of the substituent. In a meta position with respect to the Pt–CC^N bond, the substituent exerts a predominantly stabilising effect on the lowest triplet excited state that red-shifts the emission of the complex compared to the reference [Pt(ppy)(pivacac)], 1, where ppy is 2-phenylpyridinato. When the –SF5 group is located para to the Pt–CC^N bond, it does not affect the triplet state directly, and the electron-withdrawing group stabilises the metal-based orbitals, resulting in a blue-shift of the emission. In the solid-state all three complexes are mechanochromic, and can display excimeric emission originating from intermolecular π–π* interactions, but the relative emission intensities of the monomeric and dimeric excited states correlate with the steric congestion of the metal centre, and in particular the regiochemistry of the –SF5 group. We relate these findings with observations in the crystal structures.